1991
DOI: 10.1002/elps.1150120217
|View full text |Cite
|
Sign up to set email alerts
|

Databases, quality control and interpretation of DNA profiling in the Home Office Forensic Science Service

Abstract: The history of DNA profiling in the Home Office Forensic Science Service began with the introduction of multilocus probes into casework in 1986. The use of single-locus probes was introduced in 1990, supported by databases of three ethnic groups; interpretation is backed up using a Bayesian approach. Databases were compiled using an image analysis computing system. Quality control systems are described, detailing requirements before a sample can be included in the database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…There are also differences in measurement error between laboratories [25,26]. These deficiencies are accounted for by use of marker DNA fragments of known nucleotide base pair length to assist in estimating cleaved DNA fragment sizes; however, acknowledgement of remaining error of measurement of the size of detectable fragments is inherent in the application of a tolerance range for considering fragments of similar but different sizes as a "match" [27]. Laboratory error is also inherent in partial genome sequencing [28].…”
Section: Discussionmentioning
confidence: 99%
“…There are also differences in measurement error between laboratories [25,26]. These deficiencies are accounted for by use of marker DNA fragments of known nucleotide base pair length to assist in estimating cleaved DNA fragment sizes; however, acknowledgement of remaining error of measurement of the size of detectable fragments is inherent in the application of a tolerance range for considering fragments of similar but different sizes as a "match" [27]. Laboratory error is also inherent in partial genome sequencing [28].…”
Section: Discussionmentioning
confidence: 99%
“…Within any locus, there is little variation in c (except for D4S139). From casework data the value of c for YNH24 has been estimated [9] (see also [8]) to be 0.008. This value seems to agree with the average value of c estimated from data on the sample of bloodstains, excluding the data of D4S139.…”
Section: "Matching": the Current Procedures And Some Problemsmentioning
confidence: 99%
“…They performed withinperson comparisons on the duplicate results and betweenperson comparisons on the results from different individuals. They concluded that the method described by Gill et al [5] was sufficiently robust for use in forensic casework.…”
Section: Introductionmentioning
confidence: 97%
“…Gill et al [5] described the basic match/binning methodology used by the FSS. This involves a 2.8% match guideline and a corresponding 5.6% sliding window to provide a conservative estimate of database frequencies.…”
Section: Introductionmentioning
confidence: 99%